New systematic results based on chaetal hard structures in Mesochaetopterus (Polychaeta) - Bhaud, Michel; Koh, Byoung-Seoul; Martín, Daniel (Scientia Marina, 2006)
Two kinds of chaetal hard structures have been analysed within the genus Mesochaetopterus (Chaetopteridae, Polychaeta): the specialised chaetae of the fourth segment of the anterior part of the body (i.e. the A4 segment) and the uncinal plates present on neuropodia of mid and posterior parts (i.e. B- and C-regions, respectively). The examination of a large number of specimens leads to identification of finer geographic differences based on the morphological variations of these chaetal hard structures than on criteria linked to the soft body structures. These differences may be considered as species-level markers with a high degree of certainty. As a consequence, the reintroduction of M. sagittarius (Claparède, 1870) is proposed for specimens from the Atlantic and the Mediterranean Sea, while M. minutus (Potts, 1914) is retained for some specimens from the Pacific Ocean. The specimens from the Persian (= Arabian) Gulf seem to be different from those of the Indian Ocean, likely a new species of the genus. Geographic differentiation is also observed over shorter distances and two morphologies of A4 chaetae are identified on specimens from the Solomon’s archipelago, suggesting also the presence of new species. However, other taxonomically valid characters should be explored, in addition to the chaetal hard structures described herein, to formally describe these species. This research adds to the growing literature that suggests truly cosmopolitan species, specifically within the genus Meesochaetopterus and possibly within the Chaetopteridae as a whole, are increasingly difficult to find.